Bangladesh Integrated Household Survey (BIHS) 2011-2012 - International Food Policy Research Institute (International Food Policy Research Institute, 2013)
Bangladesh Integrated Household Survey (BIHS) 2011-2012 is the only nationally representative survey that has collected data on (1) plot-level agricultural production and practices, (2) dietary intake of individual household members, and (3) anthropometric measurements of all household members.The BIHS covers 6500 households in 325 primary sampling units. The sample is statistically representative at following levels: (a) nationally representative of rural Bangladesh; (b) representative of rural areas of each of the seven administrative divisions of the country: Barisal, Chittagong, Dhaka, Khulna, Rajshahi, Rangpur, and Sylhet; and (c) representative of the Feed the Future (FTF) zone of influence.